2017
DOI: 10.1242/dev.140731
|View full text |Cite
|
Sign up to set email alerts
|

Pluripotent stem cell-derived organoids: using principles of developmental biology to grow human tissues in a dish

Abstract: Pluripotent stem cell (PSC)-derived organoids are miniature, threedimensional human tissues generated by the application of developmental biological principles to PSCs in vitro. The approach to generate organoids uses a combination of directed differentiation, morphogenetic processes, and the intrinsically driven self-assembly of cells that mimics organogenesis in the developing embryo. The resulting organoids have remarkable cell type complexity, architecture and function similar to their in vivo counterparts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
163
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 250 publications
(176 citation statements)
references
References 61 publications
0
163
0
1
Order By: Relevance
“…More recently, it was shown that human optic cup organoids engrafted onto injured eyes in primates continue to differentiate into a variety of retinal cell types, even creating synaptic contacts with the host (Shirai et al, 2016). Many other examples of organoids have also emerged (reviewed by McCauley and Wells, 2017), including gut (Sato et al, 2009;Spence et al, 2011), kidney (Takasato et al, 2015), pancreas (Greggio et al, 2013) and even brain (Eiraku et al, 2008;Lancaster et al, 2013) organoids. Their generation often involves modifications to 3D culture conditions and mimicking the assumed in vivo signaling events with extrinsic factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, it was shown that human optic cup organoids engrafted onto injured eyes in primates continue to differentiate into a variety of retinal cell types, even creating synaptic contacts with the host (Shirai et al, 2016). Many other examples of organoids have also emerged (reviewed by McCauley and Wells, 2017), including gut (Sato et al, 2009;Spence et al, 2011), kidney (Takasato et al, 2015), pancreas (Greggio et al, 2013) and even brain (Eiraku et al, 2008;Lancaster et al, 2013) organoids. Their generation often involves modifications to 3D culture conditions and mimicking the assumed in vivo signaling events with extrinsic factors.…”
Section: Introductionmentioning
confidence: 99%
“…We will not focus on detailed molecular aspects of signaling and patterning nor on methods to produce organoids, as these topics have been thoroughly reviewed elsewhere (e.g. Clevers, 2016;Fatehullah et al, 2016;Kicheva and Briscoe, 2015;Lancaster and Knoblich, 2014;McCauley and Wells, 2017;Turner et al, 2016). Instead, we focus on the three ingredients that we believe are key for creating a functional organoid: (1) self-organization/assembly, which involves the correct positioning of cells with respect to one another; (2) breaking of symmetry, whereby, for instance, a seemingly homogenous cluster of cells gives rise to the body axis; and (3) the control of developmental timing and size.…”
Section: Introductionmentioning
confidence: 99%
“…Human PSC-derived organoids offer the opportunity to investigate specifically human developmental biology, as reviewed by McCauley and Wells (2017) in this issue, and thus can bring insight into how to better generate more functionally relevant cell types in vitro. With this in mind, Voges et al (2017) report on the generation of heart organoids and use them to investigate the regenerative capacity of human fetal heart tissue in vitro.…”
Section: Organoids For New Tissue Types and Improvements On Previous mentioning
confidence: 99%
“…Most of this knowledge has been gained from studying non-human vertebrate organogenesis; however, the observation that differences exist between how organs are formed across a range of species has led us to question what it is that makes us uniquely human. The revelation that human pluripotent stem cells can self-organize into three-dimensional structures that contain multiple differentiated cell types organized to resemble primary human tissue has revitalized the field of human developmental biology (McCauley and Wells, 2017). In general, these structures are referred to as organoids, and protocols have been developed to generate gut, kidney, liver bud, multiple regions of the human brain, and other tissues (McCauley and Wells, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The revelation that human pluripotent stem cells can self-organize into three-dimensional structures that contain multiple differentiated cell types organized to resemble primary human tissue has revitalized the field of human developmental biology (McCauley and Wells, 2017). In general, these structures are referred to as organoids, and protocols have been developed to generate gut, kidney, liver bud, multiple regions of the human brain, and other tissues (McCauley and Wells, 2017). Conventional strategies to analyze human organoid development often assess cell composition and differentiation using immunohistochemistry of a limited set of marker proteins, or cell tracking via a reporter gene.…”
Section: Introductionmentioning
confidence: 99%